Using ICT to Strengthen Agricultural Extension Systems for Plant Health. Issue 1 (2nd January 2016) - Wright, Holly Jane; Ochilo, Willis; Pearson, Aislinn; Finegold, Cambria; Oronje, MaryLucy; Wanjohi, James; Kamau, Rose; Holmes, Timothy; Rumsey, Abigail
ABSTRACT: Plant pests cause crop losses of 30–40%, contributing significantly to global food insecurity. The Plantwise program works alongside national agricultural extension services, who advise smallholder farmers on plant health issues and collect data on problems they face. In a 1-year pilot, Plantwise tested the use of information and communication technologies (ICT)—tablets and short message service (SMS)—with 60 Kenyan extension workers. They were able to assist more farmers with better advice, had significantly improved access to plant health information, valued being able to ask their peers for advice, and dramatically improved the quality and speed of the data they collected.